Buku Penghubung Berbasis Android Menggunakan Metode Prototyping - Heri Maulana; Kasmawi Kasmawi; Depandi Enda (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Abstract — The role of parents is very important in the education of their children, even though parents have entrusted their children to school. Parents also have responsibility for continuing children's learning at home. Parents of course need information about their child's learning at school, so that they guide learning at home in accordance with the lessons learned at school. In order for the information to be conveyed properly, SDN 04 Bengkalis uses a Buku Penghubung. Buku penghubung is used as a medium for communication between teachers and parents. However, the problem that arises from using it is the lack of interest of parents in using buku penghubung. Buku penghubung, also often left behind, easy to lose, and prone to damage because made of paper. This research aims to build an android-based buku penghubung application. The application features announcements, daily grades, list of lessons, and attendance. The method in this research is the prototyping. The result of this research is an android-based buku penghubung application that can be used by teachers and parents. Application testing uses the black box testing and compatibility testing. Keywords— Buku Penghubung, Android, Black Box, Compatibility.